LITERATUR REVIEW: REFORMASI ANGGARAN DAERAH DAN AKUNTANSI KEUANGAN DAERAH - Fuat, Faidal; Djasuli, Mohamad (Growth, 2024)
This literature study was carried out with the aim of knowing the implementation and analyzing budget and financial accounting reforms in regional government. This research uses a literature review or what is also known as a literature review. Based on the results of research conducted on the Google Scholar site, 15 articles were determined that met the criteria determined by researchers from a total review of 15,400 articles published on the Google Scholar site in the 2014-2024 period. The findings obtained from the results of the literature review are that in this post-reform era, regional budget management is required to be transparent and accountable. The financial accounting system during the reform period applies the accrual principle which is expected to produce specific, complete and informative descriptions of regional government financial reporting.